1994
DOI: 10.1093/clinids/19.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Systemic and Local Infections Due to Exophiala Species

Abstract: We report the successful treatment of three cases of infection due to Exophiala species. These organisms belong to the heterogeneous group of dematiaceous (darkly pigmented) fungi. Two cases of infection occurred in organ transplant recipients who were receiving immunosuppressive medications. Both of these infections remained localized to the subcutaneous tissues and were successfully treated with surgical excision of the lesions. We also describe what is to our knowledge the first reported case of prosthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
0
42
0
1
Order By: Relevance
“…Disseminated infection is the most uncommon manifestation of infection caused by melanized fungi. In a review of 72 cases (627), most patients were immunocompromised, though occasional patients without known immunodeficiency or risk factors developed disseminated disease as well (3,24,73,76,95,105,119,171,208,238,242,246,288,291,308,321,345,386,389,397,400,402,403,409,423,424,435,471,485,516,538,543,550,557,578,593,595,596,612,621,627,640,647,672,688,712,713,740,…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Disseminated infection is the most uncommon manifestation of infection caused by melanized fungi. In a review of 72 cases (627), most patients were immunocompromised, though occasional patients without known immunodeficiency or risk factors developed disseminated disease as well (3,24,73,76,95,105,119,171,208,238,242,246,288,291,308,321,345,386,389,397,400,402,403,409,423,424,435,471,485,516,538,543,550,557,578,593,595,596,612,621,627,640,647,672,688,712,713,740,…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Multiple reports describe the infection of organ transplant recipients on high-dose steroids and other immunosuppressive agents by Exophiala species (9,25,26,27). In addition, partial defects in cell-mediated immunity have been associated with both human infection and infection in animal models (16,17).…”
Section: Presented At the 102nd General Meeting Of The American Sociementioning
confidence: 99%
“…They found that terbinafine was the most active drug against all of the isolates. Others have reported susceptibility to commonly used antifungal agents as well (9,18; D. Whittle and I. S. Kominos, Letter, Clin. Infect.…”
Section: Presented At the 102nd General Meeting Of The American Sociementioning
confidence: 99%
“…More often chromoblastomycotic agents are described: Alternaria spp. [7], A. alternata [8,9] [ 19,201, E. spinifera [21], Phialophora parasitica [22], Phialemonium dimorphosporum or I? cuwatum and I?…”
Section: Discussionmentioning
confidence: 99%